Incidencia de fungemia en la unidad de recién nacidos del Hospital Universitario San Ignacio de Bogotá en el periodo comprendido desde el 01 de enero de 2008 hasta el 31 de diciembre de 2018 - Maria Sánchez-Tordecilla (Infectio, 2022)
Objective: To establish the incidence of neonatal fungemia and characterize the clinical variables of invasive fungal infection cases at the University Hospital of San Ignacio in Bogotá (HUSI), Colombia, between 2008 and 2018.Material and method: Case-control study nested in a retrospective cohort, with information obtained from databases of the departments of microbiology and statistics, as well as clinical records.Results: In the study period, a total of 12,905 neonates were attended; with an incidence rate of 6.2 per 10,000 patients, with an equal distribution by sex and a median gestational age of 36.5 weeks. Candida albicans was the main causal agent (50%). In the cases, the use of broad-spectrum antibiotics was reported in 75%, parenteral nutrition in 100%, previous surgical intervention in 75% (mainly gastrointestinal type 83.3%), use of central venous catheter in 100% and start of early trophic feeding in 12.5%. Remarkably the use of postnatal corticosteroids was not documented in the cases group.Conclusions: We found a low incidence of fungemia in our institution. This suggests that antifungal prophylaxis may not be advisable in our context. In the few patients with invasive fungal infection, the most frequent related condition was gastrointestinal surgical diseases. This is likely to be related to prolonged parenteral nutrition throughout central venous catheters.